Sanksi Pidana terhadap Pelanggaran Lalu Lintas yang Mengakibatkan Hilangnya Nyawa Seseorang - Maudy Aulia Putri; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Jurnal Konstruksi Hukum, 2021)
Congestion on the road is increasing nowadays, this has a huge impact on a person, the number of roads is not in accordance with the large number of vehicles this is a traffic accident. The trigger for traffic accidents is because people still lack understanding of how to drive. This study aims to explain traffic arrangements that occur to someone who reports someone's life and explain the criminal sanctions against traffic that reports someone's life. The method used is the method of normative legal research by using a technique of approaching the problem of invitation and conceptual. The data subsectors used are primary and secondary data sources. This study concludes that traffic and transport are ready to serve based on the assumptions contained in Article 316 paragraph 1 of the UULAJ. Criminal enforcement against traffic crime perpetrators is recorded in Articles 310 and 311 of the Law. The criminal investigation process at the District Court is carried out by means of a quick and simple investigation procedure.